2012
DOI: 10.3389/fnhum.2012.00128
|View full text |Cite
|
Sign up to set email alerts
|

Does the brain know who is at the origin of what in an imitative interaction?

Abstract: Brain correlates of the sense of agency have recently received increased attention. However, the explorations remain largely restricted to the study of brains in isolation. The prototypical paradigm used so far consists of manipulating visual perception of own action while asking the subject to draw a distinction between self- versus externally caused action. However, the recent definition of agency as a multifactorial phenomenon combining bottom-up and top-down processes suggests the exploration of more compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 89 publications
(110 reference statements)
5
61
2
Order By: Relevance
“…Consistent with previous studies of neural oscillations during joint attention (Lachat et al, 2012), coordination (Tognoli et al, 2007, Dumas et al, 2012, Naeem et al, 2012a, and observation (Cochin et al, 1999, Caetano et al, 2007, 10 Hz suppression was found over left-central electrodes when interacting with another person versus a nonresponsive computer, with additional frontal components. While mu-rhythm suppression is well known to occur over the bilateral sensorimotor cortex (but stronger over the contralateral cortex) when engaging in motor activity in contrast to rest (Gastaut, 1952, Gastaut and Bert, 1954, Pfurtscheller and Lopes da Silva, 1999, it has also been found during action observation (Hari et al, 1998, Cochin et al, 1999, Caetano et al, 2007, and is hence thought to be part of a common coding mechanism of perception and action (Hari, 2006, de Lange et al, 2008.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with previous studies of neural oscillations during joint attention (Lachat et al, 2012), coordination (Tognoli et al, 2007, Dumas et al, 2012, Naeem et al, 2012a, and observation (Cochin et al, 1999, Caetano et al, 2007, 10 Hz suppression was found over left-central electrodes when interacting with another person versus a nonresponsive computer, with additional frontal components. While mu-rhythm suppression is well known to occur over the bilateral sensorimotor cortex (but stronger over the contralateral cortex) when engaging in motor activity in contrast to rest (Gastaut, 1952, Gastaut and Bert, 1954, Pfurtscheller and Lopes da Silva, 1999, it has also been found during action observation (Hari et al, 1998, Cochin et al, 1999, Caetano et al, 2007, and is hence thought to be part of a common coding mechanism of perception and action (Hari, 2006, de Lange et al, 2008.…”
Section: Discussionsupporting
confidence: 91%
“…followers) and initiators (i.e. leaders) of action in reciprocal imitation paradigms in both interactive (Dumas et al, 2012, Guionnet et al, 2012) and non-interactive scenarios (Decety et al, 2002). These studies have shown activation of the inferior parietal cortex during initiation and imitation of stimuli, in the absence of interaction (Decety et al, 2002), as well as recruitment of fronto-parietal regions during interactive imitation (Guionnet et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations